EFFECTS OF PRESS PRESSURE ON GLUE LINE THICKNESS AND PROPERTIES OF LAMINATED VENEER LUMBER GLUED WITH MELAMINE UREA FORMALDEHYDE ADHESIVE - Ramazan Kurt,; Muhammet Cil (BioResources, 2012)
Laminated veneer lumbers (LVLs) were manufactured from half-round sliced I-214 hybrid poplar clone veneers with MUF adhesives using press pressures ranging from 2.5 to 15 kg cm-2. The results showed that the press pressures affected the glue line thickness (GLT) and the physical and mechanical properties of the LVLs. Higher specific gravity (SG) and mechanical properties, but lower GLT were developed as a result of using higher press pressures. The optimum press pressure was found to be 10 kg cm-2 in relation to GLT, SG, and mechanical properties. Significant linear correlations were found between GLT and mechanical properties. GLT can be used to determine the quality of wood bonding and may become a valuable tool for this purpose. Reliable data on the optimum GLT and press pressures can be used to design safe wood bonding applications in all aspects of wood based composites, as well as wood constructions when appropriate techniques are adopted to measure the GLT.